PPARα contributes to protection against metabolic and inflammatory derangements associated with acute kidney injury in experimental sepsis. Issue 10 (18th May 2019) - Iwaki, Takuma; Bennion, Brock G.; Stenson, Erin K.; Lynn, Jared C.; Otinga, Cynthia; Djukovic, Danijel; Raftery, Daniel; Fei, Lin; Wong, Hector R.; Liles, W. Conrad; Standage, Stephen W.
Abstract: Sepsis‐associated acute kidney injury (AKI) is a significant problem in critically ill children and adults resulting in increased morbidity and mortality. Fundamental mechanisms contributing to sepsis‐associated AKI are poorly understood. Previous research has demonstrated that peroxisome proliferator‐activated receptor α (PPAR α ) expression is associated with reduced organ system failure in sepsis. Using an experimental model of polymicrobial sepsis, we demonstrate that mice deficient in PPAR α have worse kidney function, which is likely related to reduced fatty acid oxidation and increased inflammation. Ultrastructural evaluation with electron microscopy reveals that the proximal convoluted tubule is specifically injured in septic PPAR α deficient mice. In this experimental group, serum metabolomic analysis reveals unanticipated metabolic derangements in tryptophan‐kynurenine‐NAD + and pantothenate pathways. We also show that a subgroup of children with sepsis whose genome‐wide expression profiles are characterized by repression of the PPAR α signaling pathway has increased incidence of severe AKI. These findings point toward interesting associations between sepsis‐associated AKI and PPAR α ‐driven fatty acid metabolism that merit further investigation. Abstract : Sepsis‐associated acute kidney injury (SA‐AKI) is a significant problem in the critically ill children. Using a mouse model of sepsis, we show that expression of PPARα, a nuclear hormone receptor transcription factor that regulates fatty acid oxidation and inflammation, protects against the development of SA‐AKI and other metabolic derangements. We also show that children with septic shock whose genome‐wide expression profiles are characterized by decreased PPARα expression have greater incidence of SA‐AKI, which points toward the exciting possibility of treating this condition with clinically available PPARα agonists.